Social protection programs: Building the evidence and defining priorities - Gilligan, Daniel O.; Ahmed, Akhter; Alderman, Harold; de Brauw, Alan; Hidrobo, Melissa; Hirvonen, Kalle; Hoddinott, John F.; Leight, Jessica; Roy, Shalini; Taffesse, Alemayehu Seyoum (International Food Policy Research Institute, 2025)
Social protection programs to reduce poverty, food insecurity, and vulnerability in low- and middle-income countries have become increasingly prominent over the last 50 years. This chapter examines trends in the development of social protection programs and discusses the contribution of research to changing program approaches and social protection policies, highlighting IFPRI’s role in providing evidence and research.